Sustainability Challenges of Fast Fashion: Environmental and Social Impacts of Cotton Growing and the Ready-Made Garment Industry in Turkey - Elif Oral (Universitas Airlangga, 2019)
Turkey is one of the main actors of the global ready-made garment manufacturing industry both as a crucial country for organic and conventional cotton cultivation and as an exporter of yarn, fabric, textile, and RMG. Being a developing country, Turkey benefits from agricultural and industrial activities as they create employment opportunities and boost the national economy and development. On the other hand, Turkey also struggles to cope with the costs of this economic growth, such as the adverse impacts on the environment and human rights. In fact, except for certain legal loopholes, Turkish labour law and relevant legislation on environmental protection are mostly harmonised with the EU standards. Therefore, the main problems, such as unregistered foremanship, unregistered employment, informal workshops, and undeclared subcontracting seem to stem from the loose enforcement of these laws due to the deficiencies in the legal system in general. Other reasons that prove to create challenges for an effective implementation and enforcement of laws include: firstly, social realities, such as an increase in population, as a result of the high birth rates, rural-urban migration, and refugee influx, which is followed by high unemployment rates; secondly, economic constraints, such as a competitive labour market, market economy, and expensive eco-friendly technology; and, finally, structural obstacles, such as the lack of advanced irrigation systems and drainage canals, all of which are examined in this study in relation to cotton cultivation and the RMG industry.